2020
DOI: 10.1007/s00705-020-04747-8
|View full text |Cite
|
Sign up to set email alerts
|

The antiviral protein viperin interacts with the viral N protein to inhibit proliferation of porcine epidemic diarrhea virus

Abstract: In the early stage of virus infection, the pattern recognition receptor (PRR) signaling pathway of the host cell is activated to induce interferon production, activating interferon-stimulated genes (ISGs) that encode antiviral proteins that exert antiviral effects. Viperin is one of the innate antiviral proteins that exert broad-spectrum antiviral effects by various mechanisms. Porcine epidemic diarrhea virus (PEDV) is a coronavirus that causes huge losses to the pig industry. Research on early antiviral respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“… Restricts viral replication and/or assembly via interactions with N proteins. [230] BST2 Inhibits the release of HCoV-229E and SARS-CoV-2 virion particles. Tethers virions on the cellular surfaces or intracellular membranes.…”
Section: Isgs That Inhibit Distinct Steps Of Hcov Replicationmentioning
confidence: 99%
“… Restricts viral replication and/or assembly via interactions with N proteins. [230] BST2 Inhibits the release of HCoV-229E and SARS-CoV-2 virion particles. Tethers virions on the cellular surfaces or intracellular membranes.…”
Section: Isgs That Inhibit Distinct Steps Of Hcov Replicationmentioning
confidence: 99%
“…During virus invasion into host cells, a series of complex interactions occurs between the virus and the host cell, including the regulation and modification of the cell by the virus and antiviral action by the cellular factors. Up to now, several antiviral factors have been explored during PEDV infection, such as bone marrow stromal cell antigen 2, transferrin receptor 1, cholesterol 25-hydroxylase, GTPase-activating protein-binding protein 1, interleukin-11, and IFN-λ [12][13][14][15][16][17][18][19]. The study of host antiviral factors can help to better understand the host-virus interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Tomatidine inhibits PEDV replication by targeting 3CL protease [14]. Viperin interacts with the viral N protein to inhibit PEDV proliferation [15]. Moreover, cholesterol 25-hydroxylase, GTPase-activating protein-binding protein 1, interleukin-11 and IFN-λ can regulate PEDV infection and replication [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Given the antagonizing role of PEDV N protein in the type I IFN response, it is not unexpected that this protein becomes a target of the host innate immune system. One study showed that viperin, an ISG induced by IRF1 and IRF3, interacts with the PEDV N protein and inhibits PEDV proliferation [ 47 ]. IRAV (IFN-regulated antiviral), BST-2 (bone marrow stromal cell antigen-2), and TRIM21 are three additional ISG proteins that have been shown to interact with the PEDV N protein [ 48 50 ].…”
Section: Pedv N Proteinmentioning
confidence: 99%